Rancang Bangun Wireless Power Transfer (WPT) Menggunakan Prinsip Resonansi Induktif Elektromagnetik dan Blocking Oscillator dengan Coil Berbentuk Spiral Mendatar - Arief Karyadi Prasojo; Indra Surjati (Jurnal Elektro, 2019)
Along with the development of the technology even more advanced and requires humans to create the latest technology to simplify and accelerate work and just a lifestyle to indulge themselves in undergoing their daily activities. Cordless power transfer is a system of power transfer without using cables that are directly connected between voltage sources and electronic devices that are expected to simplify and improve the quality of human lives. This study aims to design a wireless power transfer. In this case the method or principle of electromagnetic inductive resonance is used among several other methods including radio waves and laser light. The main results to be achieved are providing information that it turns out that energy can be channeled without using cable media directly. This wireless energy transfer proves that the energy from electromagnetic waves around us can be harvested again into alternative energy sources and this is very promising.